Perancangan Learning Management System Untuk Optimalisasi User Interface Dan User Experience Pengguna Disleksia Dengan Metode User Centered Design - Dzikri Mansyursyah Amin; Joko Riyanto (CV. Multi Kreasi Media, 2024)
SMP Negeri 5 Pasar Kemis located in Tangerang is one of the schools that has implemented a Learning Management System (LMS), namely portaldik. Based on the results of observations, SMP Negeri 5 Pasar Kemis teachers experienced confusion using portaldik. This is because the appearance and features of the application seem difficult for most teachers. The existing portaldik application still does not have adequate teacher activities in the teaching and learning process such as student assessment results, discussion forums, and attendance. Therefore, this study intends to design a UI/UX LMS design as a solution to the problems found. This design is equipped with accessibility for people with dyslexia. Data collection begins with observation. Furthermore, literature study, questionnaires, and interviews. User Centered Design (UCD) design method which consists of four stages.